Fully Endoscopic Resection of Cerebellopontine Angle Meningiomas - Setty, Pradeep; D'Andrea, Kenneth P.; Stucken, Emily Z.; Babu, Seilish; LaRouere, Michael J.; Pieper, Daniel R. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Objective To describe our operative technique and results from patients who underwent fully endoscopic resection of cerebellopontine angle (CPA) meningiomas.Design Prospective observational study.Setting A single academic institution that includes both neurosurgery and neuro-otology.Participants Eleven consecutive patients who underwent fully endoscopic resection of a CPA meningioma.Main Outcome Measures Hearing preservation, based on the American Association of Otolaryngology-Head and Neck Surgeons score as well as facial nerve preservation base on the House-Brackmann (HB) score. In addition, the extent of resection and complication rates was studied.Results All 11 patients underwent successful gross total resection, Simpson grade 2, of their meningioma, seen both intraoperatively and on postoperative imaging. Overall, 100% of patients maintained normal facial nerve function (HB 1/6). Audiometric testing revealed that 10 of 11 patients maintained either stable or improved hearing postoperatively based on Committee on Hearing and Equilibrium Guidelines for the Evaluation of Hearing Preservation in Acoustic Neuroma grade with the remaining patient retaining serviceable hearing. Tumor size ranged from 0.5 to 2.5 cm (mean: 1.54 cm). Mean operative time was 166 minutes (range: 122–207 minutes); estimated blood loss averaged 54.5 mL. Hospital length of stay ranged from 2 to 6 days (mean: 3.1 days), and a superficial wound infection was the only complication seen in one patient.Conclusion Fully endoscopic techniques can be used in CPA meningioma resection with excellent clinical results as an alternative to the traditional open microscopic approach.
Keywords: cerebellopontine angle; endoscopy; meningioma; minimally invasive neurosurgery; skull base